2020
DOI: 10.1089/lap.2019.0562
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Endoscopic Thyroid Surgery via the Oral Vestibular Approach and the Areola Approach

Abstract: Objective: To investigate the clinical efficacy and safety of endoscopic thyroidectomy through the oral vestibular approach and the breast approach. Methods: Retrospective analysis was done on clinical data of 80 patients who received an endoscopic thyroidectomy from April 2018 to March 2019. The research group had endoscopic thyroidectomy through the oral vestibular approach, whereas the control group had endoscopic thyroidectomy through the areola breast approach. Comparison between the two groups including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Lymph node clearance is another example of effectiveness. The number of CLND in the breast approach group in this study was 7.4 ± 4.8, which is comparable to the average CLND reported by other scholars [6.15 ± 4.90 ( 18 ), 7.3 ± 3.9 ( 19 ), and 7.53 ± 0.67 ( 20 )], so it is reasonable to believe that the CLND by the breast approach achieves the same extent of dissection as that reported by scholars both nationally and internationally. However, we observed that the mean number of lymph nodes in the central area of the breast approach group was lower than that of traditional open surgery on the neck [10.87 ± 6.43 ( 21 ), 10.71 ± 5.17 ( 22 ), 10.1 ± 6.98 ( 23 )].…”
Section: Discussionsupporting
confidence: 88%
“…Lymph node clearance is another example of effectiveness. The number of CLND in the breast approach group in this study was 7.4 ± 4.8, which is comparable to the average CLND reported by other scholars [6.15 ± 4.90 ( 18 ), 7.3 ± 3.9 ( 19 ), and 7.53 ± 0.67 ( 20 )], so it is reasonable to believe that the CLND by the breast approach achieves the same extent of dissection as that reported by scholars both nationally and internationally. However, we observed that the mean number of lymph nodes in the central area of the breast approach group was lower than that of traditional open surgery on the neck [10.87 ± 6.43 ( 21 ), 10.71 ± 5.17 ( 22 ), 10.1 ± 6.98 ( 23 )].…”
Section: Discussionsupporting
confidence: 88%
“…Despite an absence of local inconsistencies between the direct and indirect evaluations of most outcomes, RBAB (compared to the control: direct, SMD = 0.47 [À0. 15 45, 6.34], p = 0.0084). The outcomes "contracted" between the direct and indirect comparisons, such that any apparent advantage of RBAB or RO should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 94%
“… 6–8 We recorded the number, age, sex, nationality, treatment group, and outcomes of patients. The operative outcomes (intraoperative time, bleeding, hospitalization days, cosmetic satisfaction, postoperative drainage amount, and postoperative pain score) and complications (accidental parathyroidectomy, chyle leak, flap problems, hematoma, transient and permanent hypocalcemia, transient and permanent vocal cord palsy, tracheal injury, seroma, and wound infection) were analyzed 9–86 . The clinical studies were appraised independently by two authors, and the quality assessment of nonrandomized studies was completed using the Methodological Index for Non‐Randomized Studies (MINORS) tool 87 .…”
Section: Methodsmentioning
confidence: 99%
“… 10 Cosmetic score was measured 3 months after surgery, the clinical evaluation divisions were as follows: 0 to 3 means fair cosmetic effects, 4 to 6 means moderate cosmetic effects, and 7 to 10 means good cosmetic effects, these scores were recorded. 11 …”
Section: Methodsmentioning
confidence: 99%